SOSIALISASI PENCEGAHAN RADIKALISME PADA SISWA SMA MELALUI PENDEKATAN LITERASI BAHASA INDONESIA DI SMAN 9 PEKANBARU - Ginna Arvi Nanda; Annisa Mutia; Syakirah Permata Auliya; Naila Awalia Antoni; Syafira Atikah Putri; Rado Justeza; Iqbal Ibrahim; Yones Paulus Sinaga; Ripi Hamdani (CV. Denasya Smart Publisher, 2026)
Radicalism is a social challenge that can potentially affect adolescents, particularly senior high school students who are in a phase of identity formation. Limited literacy skills and critical thinking abilities may increase students’ vulnerability to the spread of radical ideologies through their social environment and information media. This community service activity aimed to enhance students’ understanding of radicalism and to foster critical awareness through a Bahasa Indonesia literacy approach. The activity was conducted on December 11, 2025, at SMAN 9 Pekanbaru, Jalan Semeru, involving students aged 16–18 years. The methods employed included observation of the school environment, direct socialization activities, and interactive presentations on radicalism integrated with Bahasa Indonesia learning. The material was delivered interactively to encourage active student participation. The results indicated that students gained a better understanding of the definition, characteristics, and impacts of radicalism, as well as the importance of literacy skills in filtering information. Overall, participants’ responses suggested that the activity was beneficial and relevant to their daily lives as students. This community service activity is expected to serve as a preventive effort in reducing the spread of radical ideologies in the school environment while supporting the strengthening of Bahasa Indonesia literacy.